Identification of Mathematical Anxiety among the Students of Mathematics Department in an Islamic University in Metro - Selvi Loviana (Elementary: Jurnal Ilmiah Pendidikan Dasar, 2020)
In the process of teaching and learning, students usually have an anxiety. One of the anxieties faced by students of Mathematics department IAIN Metro is the pressure of learning. In order to identify this case, the researcher did a case study research. The subject of the research was the 6th semester students of Mathematics department of IAIN Metro, who have been learning Micro Teaching. Data collecting techniques used in this research were questionnaire, interview and observation. Based on the result of the research, the anxiety was caused by the uncomfortable atmosphere of the class, the inappropriate method used by the lecturer, their low confidence, and the teacher’s stressful teaching style, students’ worry toward unsuccessful assignments and their low proficiency. This anxiety decreases the students’ concentration when doing the examination.